EVALUATION OF QUALITY OF LEARNING AND TEACHING IN HIGHER EDUCATION (LITERATURE REVIEW) - Паламарчук, Ольга (Modern engineering and innovative technologies, 2022)
Analysis of research publications shows challenges to a systematic approach of evaluation processes, balance of trust and autonomy of faculties, motivation of academic staff to professional development, ensuring student participation in evaluation and pro